Factors Affecting Buyer Decision on Tourism Business Event - Yuniati, Nining (E-Journal of Tourism; Volume 9 Number 2 (September 2022), 2022)
Not a lot of research related to the determinants that influence delegates to participate in an event. This research is related to a number of factors that influence delegates who are tourism business key players when participating in a tourism event as the case is JITM 2019 which held at Yogyakarta. These factos are including accessibility, event organizer, accommodation, venue, and perceived of prices. By observing on 100 respondent who were buyer at the event and by using classical assumption test, it was found that these five factors i.e accessibility, event organizer, accommodation, venue, and perceived of prices were indeed proven to significantly influence the decision to participate in the event. Accomodation is the most influential factor, as for the details discussed in this paper. Keywords: participation; business event; decision; MICE.